0030 Involvement Of Regulatory Factor X4 In Narcolepsy. (27th April 2018) - Luo, G
Abstract: Introduction: Type 1 narcolepsy is 98% associated with human leukocyte antigen (HLA) class II haplotype DQA1*01:02/DQB1*06:02 (DQ0602) and highly associated with T cell receptor (TCR) alpha locus polymorphism and other immune regulatory loci. During 2009–2010, a number of narcolepsy cases appeared linked to Pandemrix ® vaccination, strongly suggesting that narcolepsy is an autoimmune disorder. In spite of all the indirect evidence, the identification of the autoantigens involved remains elusive. Here we studied whether autoimmunity directed toward the transcription regulatory factor X4 (RFX4), a protein co-localized with hypocretin, is involved in narcolepsy cases. Methods: Anti-RFX4 variant 3 (RFX4_v3) autoantibodies were detected using flow cytometry and confirmed using western blotting and cell-based assay in 86 narcolepsy cases and 88 DQ0602 positive controls. T cell reactivity was examined using RFX4 peptide-DQ0602 tetramers, after screening of an overlapping peptide library for strong binders to DQ0602. RFX4 peptide-DQ0602 tetramer staining of all strong DQ0602 binders was conducted in 16 DQ0602 positive subjects (3 early onset patients, 7 post-Pandemrix ® patients, and 6 post-Pandemrix ® controls). PBMCs were stimulated and cultured for 10 days with Pandemrix ® or single peptides and stained with each tetramer. Results: Anti RFX4_v3 antibodies were found in in 2 of 86 narcolepsy patients and 1 of 88 controls. Tetramer positive cells were observed after single peptide but not Pandemrix cultures. RFX4-specific CD4+ T cells were detected in 2 post Pandemrix ® narcolepsy cases using tetramer DQ0602-RFX4-95. Staining with tetramer DQ0602-RFX4-86 was observed In 2 of 7 post-Pandemrix ® narcolepsy cases and 2 of 6 controls, both unaffected post Pandemrix family members. Both RFX4-86 and RFX4-95 were recognized by one patient. RFX4-60 showed positive tetramer staining in one early onset (non post-Pandemrix) narcolepsy patient. Tetramer positive cells were not CD25/CD127/FoxP3 positive, thus unlikely to be regulatory T cells. No visible enrichment was observed in baseline PBMC samples (without pre-culture), suggesting that tetramer positive autoreactive cells are rare. Conclusion: RFX4 CD4+ T cell auto-reactivity may be involved in narcolepsy, although staining was also observed in two controls. An extended dataset with TCR sequencing is needed to address significance. Support (If Any): No